2021
DOI: 10.1038/s41598-021-92201-3
|View full text |Cite
|
Sign up to set email alerts
|

Protein residue network analysis reveals fundamental properties of the human coagulation factor VIII

Abstract: Hemophilia A is an X-linked inherited blood coagulation disorder caused by the production and circulation of defective coagulation factor VIII protein. People living with this condition receive either prophylaxis or on-demand treatment, and approximately 30% of patients develop inhibitor antibodies, a serious complication that limits treatment options. Although previous studies performed targeted mutations to identify important residues of FVIII, a detailed understanding of the role of each amino acid and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 65 publications
(77 reference statements)
2
10
0
Order By: Relevance
“…We observed that the centrality characteristics of the AT residues are similar to those of other proteins ( Lopes et al , 2021b , 2022 ), with a few residues interacting with several others, and numerous residues taking part in only a few interactions. In particular, when we consider the degree and the betweenness together, we immediately identify an emerging pattern in the AT structure, namely, the existence of residues with high-degree and high-betweenness (HDHB), residues with low-degree and high-betweenness (LDHB) and finally, residues displaying low-degree and low-betweenness (LDLB) ( Fig.…”
Section: Resultssupporting
confidence: 56%
“…We observed that the centrality characteristics of the AT residues are similar to those of other proteins ( Lopes et al , 2021b , 2022 ), with a few residues interacting with several others, and numerous residues taking part in only a few interactions. In particular, when we consider the degree and the betweenness together, we immediately identify an emerging pattern in the AT structure, namely, the existence of residues with high-degree and high-betweenness (HDHB), residues with low-degree and high-betweenness (LDHB) and finally, residues displaying low-degree and low-betweenness (LDLB) ( Fig.…”
Section: Resultssupporting
confidence: 56%
“…To address this issue, we created an in silico network representation of the FIXa structure—a residue interaction network (RIN)—where each of its residues is a node, and two nodes are connected by an edge if they are in close proximity to each other in the FIXa 3D structure. As we reported previously for FVIII ( Lopes et al, 2021a ; Lopes et al, 2021b ), this novel representation allowed us to calculate several centrality measures of each amino acid, effectively quantifying their importance in the FIXa structure and indicating which amino acids are more or less tolerant to substitutions. To ensure the robustness of this approach, we carefully validated our in silico findings against hundreds of clinical reports associating mutations to the severity of the HB symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…This network topology can be analyzed with help of various centrality measures and helps identify structurally and functionally important nodes and edges 58 . It has been used in studying protein stability and folding, effects of mutations on protein structure, protein dynamics, allosteric regulations, identification of functionally and biologically important residues, identification of ligand binding sites, and so forth 59‐63 . Here, we make use of RIN to study the functionally important residues.…”
Section: Resultsmentioning
confidence: 99%
“…58 It has been used in studying protein stability and folding, effects of mutations on protein structure, protein dynamics, allosteric regulations, identification of functionally and biologically important residues, identification of ligand binding sites, and so forth. [59][60][61][62][63] Here, we make use of RIN to study the functionally important residues. In order to make interaction networks, we made use of the lowest energy conformations of Tau_plane and Tau_glyc obtained from the FEL analysis.…”
Section: Rin Analysismentioning
confidence: 99%